Wideband and high gain elliptically-inspired 4 × 4 MIMO antenna for millimeter wave applications - Wael A.E. Ali; Mahmoud A. Abdelghany; Ahmed A. Ibrahim (Heliyon)
An elliptically-inspired microstrip antenna is utilized in this paper to operate in the V-band (52.9–70 GHz) of the millimeter frequency range for 5G applications. 2-port and 4-port multi-input-multi-output (MIMO) configurations are designed, fabricated, and tested to validate the desired radiation and impedance characteristics. The measured results mimic the simulated ones in terms of scattering parameters, and MIMO parameters. Although the 4-port footprint is considered miniaturized (26 × 26 mm2), it provides a reduced coupling between ports (≤20 dB) with an improved gain ranging from 8 to 10.1 dBi. Furthermore, the achieved MIMO parameters (ECC, DG, CCL, and MEG) are distinct with values of 0.006, ≥9.96 dB, ≤0.4 bits/s/Hz, and −3 dB, respectively. The introduced 4-port MIMO antenna is compared with the state-of-the-art antennas and this assures that the suggested model has built-in size, wider impedance bandwidth, and higher isolation with an improved diversity characteristic confirming the possibility of the presented MIMO antenna to be a challenging candidate for 5G wireless communications.